Earnings Premiums and Penalties for Self-Employment and Informal Employees around the World - T. H. Gindling; Nadwa Mossaad; David Newhouse (Institute for the Study of Labor (IZA), 2016)
This paper examines the earnings premiums associated with different types of employment in 73 countries. Workers are divided into four categories: Non-professional own-account workers, employers and own-account professionals, informal wage employees, and formal wage employees. Approximately half of the workers in low income countries are nonprofessional own-account workers and the majority of the rest are informal employees. Fewer than 10% are formal employees, and only 2% of workers in low income countries are employers or own-account professionals. As per capita GDP increases, there are large net shifts from non-professional own account work into formal wage employment. Across all regions and income levels, non-professional own-account workers and informal wage employees face an earnings penalty compared to formal wage employees. But in low income countries, this earnings penalty is small, and non-professional own-account workers earn a positive premium relative to all wage employees. Earnings penalties for non-professional own account workers tend to increase with GDP and are largest for female workers in high income countries. Men earn greater premiums than women for being employers or own-account professionals. These results are consistent with compensating wage differentials and firm quasi-rents playing important roles in explaining cross-country variation in earnings penalties, and raise questions about the extent to which the unskilled self-employed are rationed out of formal wage work in low-income countries.
Keywords: O17; J31; J46; 330; self-employment; informal sector; earnings differentials; development